VAWG mainstreaming in access to justice programmes: a framework for action. Issue 1 (2nd January 2018) - Bradley, Tamsin; Gruber, Janet
ABSTRACT: If we are finally to end violence against women and girls (VAWG), then this commitment needs to be embedded into all development programmes, regardless of sectorial focus. Women and girls are vulnerable across the board and recognition of this reality is the first step. This article proposes a VAWG mainstreaming framework that addresses how to centralise a VAWG lens into development programming, irrespective of programmatic priorities. The article outlines the need for such a lens and presents the approach through a number of stages. The model is then applied to two programme areas, microfinance and HIV/AIDS, demonstrating its applicability across development issues.